Pengaruh Technology Readiness dan Human Resource Readiness Terhadap Kinerja UMKM di Kota Padang dengan Adoption E-Commerce sebagai Variabel Mediasi - Ochri Aulia Renza; Thamrin Thamrin (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the effect of Technology Readiness and Human Resource Readiness on MSME Performance in Padang City with E-Commerce Adoption as a mediating variable. This research is causal research. The population and samples in this study were MSME actors in Padang City. The number of samples used was 180 MSME actors who were taken by collecting data using a questionnaire with a Likert Scale. The analysis method used is SEM-PLS through SmartPLS 4.1.1 software. The results of data processing in this study indicate that: (1) Technology Readiness has a positive and significant effect on E-Commerce adoption. (2) Human Resource Readiness has a positive and significant effect on E-Commerce Adoption. (3) E-Commerce Adoption has a positive and significant effect on MSME Performance. (4) Technology Readiness has a positive and significant effect on MSME Performance. (5) Human Resource Readiness has a positive and significant effect on MSME Performance. (6) Technology Readiness has a positive and significant effect on MSME Performance mediated by E-commerce Adoption. (7) Human Resource Readiness has a positive and significant effect on MSME Performance mediated by E-commerce Adoption.